COMPARISON OF EFFICACY BETWEEN LASER AND PNEUMATIC LITHOTRIPSY FOR URETERAL STONE MANAGEMENT: A SYSTEMATIC REVIEW AND META-ANALYSIS - Wicaksono, Dillon Martino; Soebadi, Doddy Moesbadianto; Djatisoesanto, Wahjoe; Rizaldi, Fikri (Indonesian Urological Association, 2021)
Objective: This study aimed to evaluate the efficacy of ureteroscopy lithotripsy (URS) using laser lithotripsy compared to pneumatic lithotripsy for ureteral stone management. Material & Methods: A systematic search was conducted in PubMed and ScienceDirect. The search and screening process in this study followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guideline to include relevant RCTs. The included studies were assessed for their risks of bias using the Cochrane risk of bias tool 2 (RoB 2). The comparison of outcomes, which includes stone-free rate, DJ-Stent use, and mean fragmentation time between laser and pneumatic lithotripsy was analyzed using Review Manager 5.4. Results: A total of 11 RCTs evaluating a total of 235 patients with ureteral stone were analyzed in this review. Compared to pneumatic lithotripsy, laser lithotripsy has a significantly higher stone-free rate (OR 2.39, 95% CI 1.78-3.21, p < 0.001), longer mean fragmentation time (MD 4.11, 95% CI 3.17-5.04, p < 0.001), and lower DJ stent use rate (OR 0.53, 95% CI 0.36-0.76) based on the forest plot analysis. Conclusion: Patients undergoing laser lithotripsy have a higher stone-free rate, a lower DJ stent use rate, and albeit a longer mean fragmentation time compared to pneumatic lithotripsy.